Empire as the triumph of theory : imperialism, information, and the Colonial Society of 1868 - Beasley, Edward, 1964- (Cass series--British foreign and colonial policy., 2005)
A key addition to our understanding of the Victorian-era British Empire, this book looks at the founders of the Colonial Society and the ideas that led them down the path to imperialism.